Drug Delivery With Carbon-Based Nanomaterials as Versatile Nanocarriers: Progress and Prospects - Debnath, Sujit Kumar; Srivastava, Rohit (Frontiers in Nanotechnology, 2021)
With growing interest, a large number of researches have been conducted on carbon-based nanomaterials (CBNs). However, their uses are limited due to comprehensive potential environmental and human health effects. It is often confusing for researchers to make an informed choice regarding the versatile carbon-based nanocarrier system and its potential applications. This review has highlighted emerging applications and cutting-edge progress of CBNs in drug delivery. Some critical factors like enzymatic degradation, surface modification, biological interactions, and bio-corona have been discussed here. These factors will help to fabricate CBNs for effective drug delivery. This review also addresses recent advancements in carbon-based target specific and release controlled drug delivery to improve disease treatment. The scientific community has turned their research efforts into the development of novel production methods of CBNs to make their production more attractive to the industrial sector. Due to the nanosize and diversified physical properties, these CBNs have demonstrated distinct biological interaction. Thus long-term preclinical toxicity study is recommended before finally translating to clinical application.